Conceptual design methodologies appropriate to electric vertical take-off and landing aircraft in urban air mobility - Peng, Quan (Cranfield University, 2023)
This project aims to investigate the current state of conceptual design issues related to electric Vertical Take-off and Landing aircraft (eVTOL) in Urban Air Mobility (UAM). The thesis seeks to develop design methodologies appropriate for eVTOLs and explore the design space for various configurations, including Vectored Thrust, Lift+Cruise, and Multicopter concepts. This project developed a design model for eVTOL within the multi-disciplinary design analysis and optimization environment - GENUS at Cranfield University. The GENUS framework integrates various aerodynamic analysis tools, efficient geometric parameterization methods, semi-empirical mass breakdown models, and effective boundary layer ingestion analysis models. This enables comprehensive conceptual design and design space exploration for novel aircraft, considering real-world considerations. In this project, optimization and comparison are conducted across more than 200 cases involving different aircraft configurations, passenger capacities, battery capacities, cruising speeds, and ranges. Multicopter configurations are suited for short-range, low-speed flights due to the simpler structure and rotor system, despite limitations in range and speed imposed by disk loading and propeller efficiency. Vectored Thrust configurations are suitable for long-range and high-speed flights due to the high lift-to-drag ratio. The Lift + Cruise configuration is versatile due to the combination of lift rotors and propulsion propellers, resulting in higher efficiency for both cruising and hovering. Battery technology is a crucial factor in eVTOL design. With a battery energy density of 300 Wh/kg, the battery weight accounts for approximately 60% of the total weight for a 2-passenger eVTOL undertaking a 200-mile mission. However, at a battery energy density of 900 Wh/kg, the battery weight for a 20-passenger eVTOL performing a 200-mile mission reduces to around 15-20%.
Stockford, Jack - Associate Supervisor
Keywords: Aircraft conceptual design; Multidisciplinary design optimization; electric Vertical Take-off and Landing aircraft; Urban Air Mobility; vectored thrust; lift and cruise; multicopter